Tendenciák, formai analógiák a képzőművészeti és tervezőgrafikai eszköztárban - Szekeres Ferenc; Tudományos és művészeti műhelymunkák : új utakon a pedagógusképző kar (2007) (Szeged) (2009)
There are analogies found in the history and stylistie changes of both grandart and graphic design. Alternative rational earth life-oriented „constructive viewpoint” periods, and emotional, spiritual, religious-mythological „deconstructive viewpoint” periods, are equally characteristic of both. In art history, period boundaries match boundaries of broad periods of style. In graphic design, the first loose period was followed by a more rational, editor-principled approach in the 1960’s and, after that, a more intuitíve, deconstructive approach in the second half of the 1980’s. Both in visual árts and in the rational period of graphic design there is a joint intention to bring visual Creative work to a higher level through the of conscious construction and by applying the tools of geometry.